MARKET REACTION TO THE INCRAESE IN FUEL OIL (BBM) PRICES IN 2022: EMPIRICAL STUDY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (BEI) - Nanda Nanda; Heriyadi Heriyadi; Wendy Wendy; Mustarudin Mustarudin; Mazayatul Mufrihah (SEAN Institute, 2023)
The main goal of this research is to assess the influence of the 2022 rise in fuel oil (BBM) prices on the manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research methodology consists of a Mann-Whitney U-Test and an event study. The selection for this study consists of manufacturing companies that are publicly listed on the Indonesia Stock Exchange (IDX). The research incorporates the following variables: trading volume activity (TVA), abnormal return, stock price, and stock trading frequency. The observation period is comprised of the time between the event period and the estimation period. The event period encompasses the five days preceding, one day during, and five days following the BBM fee increase. The Market Model uses the estimation period to calculate the expected return. The results of this research indicate a statistically significant variation in the abnormal return; however, no such distinctions are observed in the stock price, TVA, or stock frequency.